STRATEGIC ANALYSIS OF THE DEVELOPMENT OF UMKM "SEBLAK SELLING" IN IMPROVING COMPETITIVENESS IN THE DIGITAL ERA: ANALISIS STRATEGI PENGEMBANGAN UMKM “JUALAN SEBLAK” DALAM MENINGKATKAN DAYA SAING DI ERA DIGITAL - Kayla Alfia Azzaidi Nst; Tisragil Aprillia; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This research aims to analyse the development strategy of MSMEs "Selling Seblak" in facing competition in the digital era. Digitalisation requires MSMEs to be able to utilise social media, online ordering platforms, and product innovations in order to maintain and increase competitiveness. This research uses a qualitative descriptive method through observation, light interviews with business actors, and literature studies. The research results show that the main effective strategies include the utilisation of digital marketing, improving product quality and variety, optimising customer service, and the use of delivery applications such as GoFood and GrabFood. The implementation of this strategy is proven to increase business visibility, expand market reach, and increase the number of customers. Thus, the utilisation of digital technology becomes an important factor in the development of MSMEs to remain competitive in the increasingly dynamic culinary market.